Application of Multi-Objecttive Optimazation on the basis of Ratio Analysis in Determining Monthly Study Agenda onMasjid Al-Muhajirin Rumah Pondok Mansion - Saidi Ramadan Siregar; Pristiwanto Pristiwanto (Sean Institute, 2021)
Pondok Mansion House (RPM) which is located in the Namorambe sub-district, Deli Serdang Regency is one of the government subsidized housing held by PT Rapy Ray. The construction of the mosque which has been completed provides good news for the Muslim residents of the housing because they can carry out routine prayers and various other Islamic holiday activities. On Saturday, June 19, 2021, a mosque committee was formed before the establishment of the Mosque Prosperity Agency. Then after the mosque committee was formed. The mosque committee held a meeting to find the name of the mosque and to complete the management of the mosque which was held on July 7, 2021. To make the mosque agenda, it was discussed again by inviting members of the management which coincided on August 3, 2021. Then the results of the meeting were agreed upon by the mosque management and the problem that occurs is the emergence of disagreements or disagreements on one of the mosque's agenda schedules resulting in small talks in the housing complex area which can result in disorganization between mosque administrators and individuals who do not agree with the agenda. It is necessary to make a policy in preparing a schedule with a scientific system based on mathematical calculations so that the results can provide explanations and can be accepted with grace. Of course the well-known system in this case is the Decision Support System (DSS) in which this system provides suggestions, input, as well as contributions to organizational actors, associations whose nature is to choose the best among several available options. Then the results will provide solutions in the form of approaches with alternative systems, ratings and several components related to DSS. The value of the approach or result that will be given later reaches 80% to 95%..